Lexical characteristics of comparative constructions in Uzbek - Abduganiyeva Gulizoda Ziyod kizi, I.U.Minniqulov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Comparative constructions are pivotal in linguistics, offering insights into the interplay of morphology, syntax, and semantics across languages. This study focuses on the lexical characteristics of comparative constructions in the Uzbek language, a member of the Turkic linguistic family. Uzbek employs a diverse range of morphological markers, syntactic structures, and lexical elements to express relationships of comparison, equality, and inequality, such as suffix -roq, analytical markers such as qaraganda and ko„ra, and equative terms like dek and kabidir. This article examines the historical evolution of these markers, their dialectal variations, and their unique contributions to Turkic typology.